How to get noWear? – A new take on the design of in-situ formed high performing low-friction tribofilms. (May 2020) - Kohlhauser, B.; Ripoll, M.R.; Riedl, H.; Koller, C.M.; Koutna, N.; Amsüss, A.; Hutter, H.; Ramirez, G.; Gachot, C.; Erdemir, A.; Mayrhofer, P.H.
Abstract: Despite growing environmental concern, combustion engines are projected to stay the main technology of transportation for many years, so will unpopular S- and P- containing additives in lubricating oils. Therefore, it is essential to maximize efficiency and minimize the harmful impacts of these additives in the meantime. Coatings based on Mo and W hold great promise as they can chemically interact with S-bearing additives and form low friction tribofilms like MoS2 and in particular WS2 . Here we highlight the reaction pathways involving first the formation of oxide intermediates, followed by the generation of a highly protective and low-shear transition metal disulfide tribofilm on a tailored WN-based coating, affording coefficients of friction as low as 0.05 combined with an extraordinary wear protection (i.e., no measurable wear on sliding surfaces even after 100 h of testing). High resolution TEM and Raman spectroscopy confirm the formation of WS2 sheets and hence the huge potential of these coatings for lubricated surfaces. Graphical abstract: Unlabelled Image Highlights: In-situ formation of WS2 tribofilms on WN based coatings with S-containing additives Influence of p, T and S-content on the formation of WS2 via an intermediate oxide step during the in-situ lubrication In-situ formed WS2 based tribofilms lead to coefficients of friction of 0.05 with no noticeable wear after 100 h